Bioremediation of Aquaculture Wastewater Using Microalgae Chlorella vulgaris (2017)
Microalgae have received increasing attentions as an alternative treatment approach to remediate wastewater for both nutrient removal and biomass production. Wastewater from aquaculture industry contains high levels of nitrogen and phosphorus, which affect plant growth. Conventional methods for treating aquaculture wastewater generally are inefficient and unprofitable. In this work, microalgae Chlorella vulgaris growth was studied in aquaculture effluent medium in order to reduce its contents of NO3 and PO4. Furthermore, the effect of NaHCO3 and Na2CO3 concentrations and addition time on biomass productivity was evaluate to determine the most suitable conditions for biomass growth. It was found that highest biomass content (0.3 g/L) was achieved at 3.4 g/L of sodium bicarbonate concentration and 19 h of addition time.